2016
DOI: 10.1038/ejhg.2016.5
|View full text |Cite
|
Sign up to set email alerts
|

Congenital protein losing enteropathy: an inborn error of lipid metabolism due to DGAT1 mutations

Abstract: Protein-losing enteropathy (PLE) is a clinical disorder of protein loss from the gastrointestinal system that results in hypoproteinemia and malnutrition. This condition is associated with a wide range of gastrointestinal disorders. Recently, a unique syndrome of congenital PLE associated with biallelic mutations in the DGAT1 gene has been reported in a single family. We hypothesize that mutations in this gene are responsible for undiagnosed cases of PLE in infancy. Here we investigated three children in two f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 23 publications
3
47
0
1
Order By: Relevance
“…Further, we found a negative correlation of DGAT1 mRNA levels with many UPR genes in adipose tissue of fasted human subjects. In previous studies, we and others found that homozygous DGAT1 loss-of-function mutations in humans leads to a severe congenital diarrheal disorder involving enterocyte dysfunction, which is triggered by a fat-containing diet (Gluchowski et al, 2017; Haas et al, 2012; Stephen et al, 2016). Similarly, DGAT1 inhibition caused dose-related diarrhea in clinical studies of humans (Denison et al, 2014; Meyers et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Further, we found a negative correlation of DGAT1 mRNA levels with many UPR genes in adipose tissue of fasted human subjects. In previous studies, we and others found that homozygous DGAT1 loss-of-function mutations in humans leads to a severe congenital diarrheal disorder involving enterocyte dysfunction, which is triggered by a fat-containing diet (Gluchowski et al, 2017; Haas et al, 2012; Stephen et al, 2016). Similarly, DGAT1 inhibition caused dose-related diarrhea in clinical studies of humans (Denison et al, 2014; Meyers et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Deficiency in DGAT1 is a recently recognized, serious cause of neonatal diarrhea. Since its description in 2012, three genetic mutations have been identified resulting in variable phenotypes of this disease, and suggesting that, like many cases of congenital diarrhea diagnoses, there remains much to learn regarding the presentation, prevalence and etiology of DGAT1 mutation-driven diarrhea 57 . Despite the growing recognition of congenital diarrheal pathologies, and the increasing diversity of diagnosis resulting in significant diarrheal disease, the establishment of in vitro models to study the physiology behind these and other diseases remains elusive in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Dgat2 is present at significantly lower levels compared to Dgat1 in the intestine of mice, and whether DGAT2 is expressed in human intestine is questionable [6]. One of the reasons for this is that a DGAT1 loss of function mutation has been identified in humans and observed to cause congenital diarrheal disorder resulting in severe outcomes [68, 69]. Dgat1 − / − mice, on the other hand, have no obvious increase in fecal fat or diarrhea, and their intestine phenotype contributes to their beneficial resistance to diet induced obesity [16, 18, 19].…”
Section: Discussionmentioning
confidence: 99%